Investigating Measures, Challenges and Possible Solutions for Protecting Endangered Birds Species Around Lake Chilwa Ramsar Site in Malawi - Banda, Susan; Mwenda, Denis; Majamanda, James (Journal of Sustainable Natural Resources, 2025)
This study was conducted to investigate measures, challenges and possible solutions established when protecting the endangered bird species around Lake Chilwa Ramsar site. Lake Chirwa is a shallow basin lake located in the south eastern region of Malawi. It is the second largest lake in Malawi and the twelfth largest in Africa. Lake Chilwa was designated as a wetland of international importance in November 1997 (Ramsar site No. 869). Its wetland is approximately 2310 km2 and it is a home for various bird species whose lives are endangered because of the high demand for the wetland’s resources. The drying out of the lake forced inhabitants who depended on it for fish to hunting birds. In order to protect the endangered bird species, Leadership for Environment and Development (LEAD) of Malawi in collaboration with communities around intervened with measures to protect endangered bird species. This study aimed at investigating the effectiveness of these measures. Data was collected through in-depth interviews and focus group discussions. Findings show that the effectiveness of the measures to protect endangered birds species depend on collaborative efforts of various stakeholders and involvement of the local inhabitants of the area. Interventions such as civic education, natural habitat restoration, creation of sanctuaries, annual closed season and patrolling of sanctuaries by game rangers have proven to be the most effective. However, the study found that these measures were effective when LEAD project was in place and became less effective when the project pulled out. The study further found that conflict of interest, encroachment and poaching, lack of resources and resistance to change by some inhabitants negatively affect implementation of the interventions in the wetland.